Using ethnography and assemblage theory in political geography. Issue 10 (21st July 2020) - Ghoddousi, Pooya; Page, Sam
Abstract: While the focus on the 'everyday' in qualitative human geography has greatly increased the need for, and relevance of, ethnographic methods, Megoran argued that this is particularly true for political geography as it has the potential to challenge its focus on elite discourse, allowing researchers to bring forward multiple voices to investigate the becoming of political events. More recently, assemblage theory has gained traction in political geography, not only because of its capability to include the role of the material and the affective, but also revealing the links between micro‐ and macro‐politics by showing how agency emerges out of complex relations. In the first part of this paper, we present an overview of the recent uses of ethnography in political geography that have not embraced assemblage. Second, we explore the theoretical conceptualisations of, and opportunities provided by, an assemblage approach. Third, we go through the use of assemblage ethnographies in political geography, with a particular focus on Pooya's experience of research with Iranians in London. In this, he embraced a variety of ethnographic approaches, including 'auto‐ethnography', 'netnographies', 'participant sensation', in combination with observations, participatory workshops and activism. Showing the role of ethnography as a qualitative tool for political geographers to interrogate discursive social constructions, we argue that it holds even more promise for analysing and intervening in the emergent politics of socio‐material‐affective assemblages.